THE ROLE OF PHYSICAL EXPERIMENTS IN DEVELOPING STUDENTS’ DEEP THINKING SKILLS - Tursunova Shakhrizoda Panjiboy qizi (TADQIQOTLAR, 2025)
Abstract This article comprehensively analyzes the role of physical experiments in physics classes in forming students’ deep (comprehensive, systematic, and critical) thinking skills. It highlights the effectiveness of integrating theoretical and practical aspects of physics, interactive and problem-based teaching technologies, the STEAM approach, visual experiments, and project-based activities in developing students’ analytical thinking, observation skills, logical reasoning, and problem-solving abilities based on scientific sources and pedagogical experiences.